The q-Chlodowsky and q-Szasz-Durrmeyer Hybrid Operators on Weighted Spaces - Harun Çiçek; Aydın İzgi (Journal of Mathematics)
The main aim of this article is to introduce a new type of q-Chlodowsky and q-Szasz-Durrmeyer hybrid operators on weighted spaces. To this end, we give approximation properties of the modified new q-Hybrid operators. Moreover, in the weighted spaces, we examine the rate of convergence of the modified new q-Hybrid operators by means of moduli of continuity. In addition, we derive Voronovskaja’s type asymptotic formula for the related operators.